ANALISIS SISTEM INFORMASI AKUNTANSI DALAM PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (Studi Kasus Desa Karacak Kecamatan Leuwiliang Kabupeten Bogor) - Angginun Juwita Sari Harahap (2023)
This research is a qualitative research that aims to identify and explain the application of accounting information systems in managing village income and expenditure budgets and to identify constraints and solutions to the application of accounting information systems in managing village income and expenditure budgets in Karacak Village, Leuwiliang District, Bogor Regency. The SIA used by the Village is the SiskeuDes application. The application of SIA in the management of APBDes is measured based on the SIA components proposed by Romney & Steinbart, SIA performance based on the TAM theory with measurement components proposed by James Wetherbe, and internal control components based on the Committee of Sponsoring Organizations of Treadway Commission (COSO). Furthermore, the constraints on implementing SIA in managing APBDes are measured from internal control based on COSO and stages of APBDes management. This study uses an interpretive paradigm with a phenomenological approach. Data collection techniques in this study were interviews with key informants and supporting informants, as well as documentation. Overall the results of this study indicate that the Karacak Village Government has implemented SIA in managing APBDes in accordance with Permendagri/20/2018 by measuring the SIA components, SIA performance, and internal control components, in addition to the obstacles encountered in implementing SIA in managing APBDes related with the planning of APBDes and internal control. Keywords: Accounting Information System, APBDes Management, Internal Control, SiskeuDes Application, Accounting Information System Performance.